Attributes of islamic labels in increasing internal comprehensive strength - Diana Hasyim; Kustoro Budiarta; Nurul Wardani; Edison Parulian (Institute of Computer Science (IOCS), 2023)
The objectivity of this study includes 3 (three) investigations, namely (1) the implications of Islamic label attributes on financial flexibility, (2) the impact of a combination of Islamic labels and capital structure conservatism on financial flexibility, and (3) the interaction of Islamic labels and cash holding on financial flexibility. By observing 225 companies during the period 2012 – 2021 and using the Generalized Method of Moment (GMM) analysis technique, the results of the study found that the attribute of the Islamic label contributed to financial flexibility. Examination of the impact of the combination of Islamic Label (IL) and capital structure conservatism on financial flexibility shows that IL capital structure conservatism does not contribute to an increase in financial flexibility. However, cash holding IL has the potential to become a source of financial flexibility.